Are exporters more productive than non- exporters? - David A. Rivers (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2013)
In an effort to explain the observed heterogeneity in the exporting decisions of firms, the empirical trade literature has concluded that exporting firms are more productive than non-exporting firms. In this paper, I show that the foundation for this conclusion is weak, given that the productivity estimates used in the literature suffer from several sources of potential bias. I apply a new method for estimating production functions to control for these sources of bias. Using data on manufacturing firms in Colombia, I find that, while the measures of productivity used in the literature imply that exporters are more productive, once I correct for the bias, there is no correlation between productivity and export status. This result is inconsistent with productivity being the main determinant of entry into export markets, and suggests the importance of other sources of heterogeneity in explaining firm-level exporting decisions.
Keywords: 330